Terahertz emitter based on dipolaritons - Kyriienko, Oleksandr (2014)
We study the system with dipolaritons - mixed quasiparticles which are formed in the double quantum well heterostructure in the presence of strong light-matter interaction. These quasiparticles possess large dipole moment due to the resonant coupling between direct and indirect excitons via electronic tunnelling. Using the pulsed pumping of the cavity mode one can induce oscillations of the indirect exciton density. This corresponds to a harmonic change of the dipole moment in time and results in the classical electromagnetic wave emission with frequency being in the terahertz (THz) range. In the current paper we present a simple theory which describes this phenomenon and estimate possible output power of radiation.